2022
DOI: 10.1186/s13071-022-05496-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-watershed distribution pattern challenging the elimination of Oncomelania hupensis, the intermediate host of Schistosoma japonicum, in Sichuan province, China

Abstract: Background Snail control is critical to schistosomiasis control efforts in China. However, re-emergence of Oncomelania hupensis is challenging the achievements of schistosomiasis control. The present study aimed to test whether the amphibious snails can spread across watersheds using a combination of population genetics and geographic statistics. Methods The digital maps and attributes of snail habitats were obtained from the national survey on O. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This is consistent with the above results. We therefore raised the hypothesis that due to an annual flooding occurring along the Yangtze River, coupled with the movement ecology of O. hupensis , the 2014 snail population in the new emerging habitat might come from its upper reaches nearby, as Taicang of Jiangsu is connected via several canals to the river and snail dispersal may occur along the waterways [ 41 , 42 , 43 ]. The 2015 population, which might be descended from the 2014, may have spread and then form the 2016 and the 2017, the latter of which might have been missed in the local snail survey performed in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the above results. We therefore raised the hypothesis that due to an annual flooding occurring along the Yangtze River, coupled with the movement ecology of O. hupensis , the 2014 snail population in the new emerging habitat might come from its upper reaches nearby, as Taicang of Jiangsu is connected via several canals to the river and snail dispersal may occur along the waterways [ 41 , 42 , 43 ]. The 2015 population, which might be descended from the 2014, may have spread and then form the 2016 and the 2017, the latter of which might have been missed in the local snail survey performed in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…However, the AIS was only 66.10 million m 2 (or 1.85%). The snail habitats are often the small ditches around farmland either in plains or on terraces [ 41 ]. The transformation from rice paddies to dryland in some mountainous areas showed good effectiveness in snail control and schistosomiasis transmission interruption [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The habitats with a high risk of schistosomiasis transmission should be identified, and these populations should be disposed of in a most reasonable method. Watershed ecological approaches can be used in planning [ 41 , 46 ]. Secondly, technological breakthroughs in snail control are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Human population dynamics are often considered to be a major contributor to altering the natural environment. In addition, humans can also directly bring snails to other areas for dispersal, such as the construction of flood control embankments, transportation of seeds, and ditch irrigation [ 50 , 51 ]. The NLI has been applied to assess ecological status, as it reflects the level of urbanization and acts as an indicator of human activity [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a snail survey conducted in 2021 found that Changtou village of Heqing County ranked first in terms of recurrence of O. hupensis among the 32 villages investigated in 18 endemic counties [ 56 ]. Meanwhile, it is worth noting that our prediction model also found additional suitable regions where O. hupensis has so far been unrecorded but may require further investigation, including Yongping County and Longyang District, due to the possibility of human activities introducing snails into areas suitable for their survival, thus facilitating their dispersal [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%